Barriers and facilitators to sitting less at work in different organisations: a qualitative study. (November 2018) - Mackenzie, Kelly; Such, Elizabeth; Norman, Paul; Goyder, Elizabeth
Abstract: Background: Long-term sitting is associated with increased risks of chronic disease and premature mortality. Since workplaces contribute to a large proportion of daily sitting time, reducing sitting in the workplace is a relevant public health objective. To develop effective interventions, factors that can influence reduced sitting behaviour at work must be understood. This study aimed to explore these barriers and facilitators and determine how they might differ by organisation type. Methods: Four organisations based in Yorkshire, UK, which varied by size and sector, were opportunistically selected to participate; they included a local authority, corporation, charity, and small business. Convenience samples of office-based employees (n=40) were then recruited via email. Focus groups (n=10) took place in participants' workplaces and were audiorecorded and transcribed verbatim. Data were coded and thematically analysed. Further analysis explored differences in barriers and facilitators across the four organisations. Findings: Four main themes were identified—namely, factors at the individual, social, organisational, and environmental level. Many of the themes were consistent across the four organisations, but there were some key discrepancies. Organisational-level factors were less pronounced in the small business, where subthemes relating to presenteeism, the role of managers, or the ways of working were not raised, but were common among the other organisations. Social-level factors, such as "doing things as a group", were key facilitators for sitting less in the small business compared with the other organisations. Interpretation: These finding demonstrate a variety of barriers and facilitators to sitting less at work, which can vary by organisation. Variations can be explained by organisation size, structure or culture. When developing sit less at work interventions, it is important to understand an organisation's barriers and facilitators to sitting less so that these can be addressed or harnessed by the intervention. The need to understand organisation-specific barriers and facilitators may also be relevant to other workplace health promotion initiatives. Funding: Supported by the National Institute for Health Research (NIHR) (doctoral research fellowship for KM DRF-2016-09-023). The funder was not involved in the design of the study, or the collection, analysis, and interpretation of data, or in writing the abstract.